Conformational and functional variants of CD44-targeted protein nanoparticles bio-produced in bacteria. (14th April 2016) - Pesarrodona, Mireia; Fernández, Yolanda; Foradada, Laia; Sánchez-Chardi, Alejandro; Conchillo-Solé, Oscar; Unzueta, Ugutz; Xu, Zhikun; Roldán, Mónica; Villegas, Sandra; Ferrer-Miralles, Neus; Schwartz, Simó; Rinas, Ursula; et al.
Abstract: Biofabrication is attracting interest as a means to produce nanostructured functional materials because of its operational versatility and full scalability. Materials based on proteins are especially appealing, as the structure and functionality of proteins can be adapted by genetic engineering. Furthermore, strategies and tools for protein production have been developed and refined steadily for more than 30 years. However, protein conformation and therefore activity might be sensitive to production conditions. Here, we have explored whether the downstream strategy influences the structure and biological activities, in vitro and in vivo, of a self-assembling, CD44-targeted protein-only nanoparticle produced in Escherichia coli . This has been performed through the comparative analysis of particles built from soluble protein species or protein versions obtained by in vitro protein extraction from inclusion bodies, through mild, non-denaturing procedures. These methods have been developed recently as a convenient alternative to the use of toxic chaotropic agents for protein resolubilization from protein aggregates. The results indicate that the resulting material shows substantial differences in its physicochemical properties and its biological performance at the systems level, and that its building blocks are sensitive to the particular protein source.